Connexin 46 and connexin 50 gap junction channel properties are shaped by structural and dynamic features of their N‐terminal domains. (13th May 2021) - Yue, Benny; Haddad, Bassam G.; Khan, Umair; Chen, Honghong; Atalla, Mena; Zhang, Ze; Zuckerman, Daniel M.; Reichow, Steve L.; Bai, Donglin
Abstract : Key points: Gap junctions formed by different connexins are expressed throughout the body and harbour unique channel properties that have not been fully defined mechanistically. Recent structural studies by cryo‐electron microscopy have produced high‐resolution models of the related but functionally distinct lens connexins (Cx50 and Cx46) captured in a stable open state, opening the door for structure–function comparison. Here, we conducted comparative molecular dynamics simulation and electrophysiology studies to dissect the isoform‐specific differences in Cx46 and Cx50 intercellular channel function. We show that key determinants Cx46 and Cx50 gap junction channel open stability and unitary conductance are shaped by structural and dynamic features of their N‐terminal domains, in particular the residue at the 9th position and differences in hydrophobic anchoring sites. The results of this study establish the open state Cx46/50 structural models as archetypes for structure–function studies targeted at elucidating the mechanism of gap junction channels and the molecular basis of disease‐causing variants. Abstract: Connexins form intercellular communication channels, known as gap junctions (GJs), that facilitate diverse physiological roles, from long‐range electrical and chemical coupling to coordinating development and nutrient exchange. GJs formed by different connexin isoforms harbour unique channel properties that have not been fully defined mechanistically. Recent structural studies on Cx46 and Cx50 defined a novel and stable open state and implicated the amino‐terminal (NT) domain as a major contributor for isoform‐specific functional differences between these closely related lens connexins. To better understand these differences, we constructed models corresponding to wildtype Cx50 and Cx46 GJs, NT domain swapped chimeras, and point variants at the 9th residue for comparative molecular dynamics (MD) simulation and electrophysiology studies. All constructs formed functional GJ channels, except the chimeric Cx46‐50NT variant, which correlated with an introduced steric clash and increased dynamical behaviour (instability) of the NT domain observed by MD simulation. Single channel conductance correlated well with free‐energy landscapes predicted by MD, but resulted in a surprisingly greater degree of effect. Additionally, we observed significant effects on transjunctional voltage‐dependent gating ( V j gating) and/or open state dwell times induced by the designed NT domain variants. Together, these studies indicate intra‐ and inter‐subunit interactions involving both hydrophobic and charged residues within the NT domains of Cx46 and Cx50 play important roles in defining GJ open state stability and single channel conductance, and establish the open state Cx46/50 structural models as archetypes for structure–function studies targeted at elucidating GJ channel mechanisms and the molecular basis of cataract‐linked connexin variants. Key points: Gap junctions formed by different connexins are expressed throughout the body and harbour unique channel properties that have not been fully defined mechanistically. Recent structural studies by cryo‐electron microscopy have produced high‐resolution models of the related but functionally distinct lens connexins (Cx50 and Cx46) captured in a stable open state, opening the door for structure–function comparison. Here, we conducted comparative molecular dynamics simulation and electrophysiology studies to dissect the isoform‐specific differences in Cx46 and Cx50 intercellular channel function. We show that key determinants Cx46 and Cx50 gap junction channel open stability and unitary conductance are shaped by structural and dynamic features of their N‐terminal domains, in particular the residue at the 9th position and differences in hydrophobic anchoring sites. The results of this study establish the open state Cx46/50 structural models as archetypes for structure–function studies targeted at elucidating the mechanism of gap junction channels and the molecular basis of disease‐causing variants.